Double trouble! Concomitant distal ulna fractures predict worse 1-year outcome in distal radius fractures: a registry-based cohort study of 5,536 patients - Linnea Arvidsson; Marcus Landgren; Anna Kajsa Harding; Antonio Abramo; Magnus Tägil (Acta Orthopaedica)
Background and purpose: Data on distal radius fractures (DRFs) with concomitant metaphyseal distal ulna fractures is limited. We aimed to determine whether a combined DRF and distal ulna fracture (DRUF) predicts a worse patient-reported outcome, measured by the Disabilities of the Arm, Shoulder, and Hand (DASH) score, 1 year after injury. Methods: This prospective registry-based cohort study included 5,536 adult patients with a DRF between 2003 and 2018. The 1-year DASH scores were recorded. All DRUFs were identified. Multivariable binary logistic regression assessed whether the presence of a distal ulna fracture predicted a 1-year DASH score > 35, indicating severe upper-extremity symptoms. Results: 259 of 5,536 patients (4.7%) had a DRUF. Their mean age was 73 years (SD 15), and 86% were women. The median 1-year DASH score was higher in the combined fracture group compared with those with a DRF only (23, interquartile range [IQR] 5–45] vs 9, IQR 2–27, P < 0.001). A DRUF increased the odds of a 1-year DASH > 35 by 97% (OR 1.97, 95% confidence interval [CI] 1.40–2.75, P < 0.001). Surgical fixation of the DRF in DRUF patients was associated with lower odds of a worse outcome (OR 0.44, CI 0.23–0.85, P = 0.02). Distal ulna fracture fixation did not affect 1-year DASH (P = 0.7). Conclusion: The odds of having a DASH > 35, indicating severe symptoms, almost doubled at 1 year in patients with a DRUF compared with those with a DRF only.